2016
DOI: 10.1590/0100-29452016022
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of Açaí Plants Under Shade Gradation

Abstract: In order to evaluate the effect of different levels of shading on açai (Euterpe oleracea Mart.) plants development, an experiment was conducted at the Viveiro da Floresta, Rio Branco, AC. The experiment was arranged in a completely randomized design with six treatments and four replications of 25 plants, set as full sunlight and 18%, 35%, 50%, 70%, and 80% shading. The evaluation occurred 125 days after transplantation and the variables were stem diameter, root length, length of the aerial part, total length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
4
13
0
3
Order By: Relevance
“…Results observed by Dapont et al (2016) confirm that assai seedlings (E. oleracea) present a higher total dry mass in shades of 20% to 50%. In Euterpe edulis seedlings submitted to environments of 70% to 96% luminosity, a greater increase of dry mass was verified in the seedlings (Nakazono et al, 2001).…”
Section: /10supporting
confidence: 54%
See 3 more Smart Citations
“…Results observed by Dapont et al (2016) confirm that assai seedlings (E. oleracea) present a higher total dry mass in shades of 20% to 50%. In Euterpe edulis seedlings submitted to environments of 70% to 96% luminosity, a greater increase of dry mass was verified in the seedlings (Nakazono et al, 2001).…”
Section: /10supporting
confidence: 54%
“…In the literature, the cultivation environment and the nutritional question for producing assai seedlings has already been addressed. Conforto & Contin (2009) verified that the development of assai palms in the nursery phase was considered satisfactory under conditions of 50% of the incident radiation, a result corroborated by Zancheta et al (2013) and Dapont et al (2016). Mendonça et al (2006) concluded that the use of the substrate formed by plantmax + coffee bean peels + sawdust + sand and soil in the proportion of 1:1:1:1:2 v/v associated with a slow release fertilizer dose of 4 kg m -3 is a good alternative for producing an assai palm seedling grove.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The environment in which the seedlings are produced is of utmost importance, because their adaptation to it will depend on how well their photosynthetic apparatus is adjusted to this environment, in a way that the available daylight can be more efficiently used (Silva et al 2007). In this regard, some studies have been carried out, for instance, addressing E. oleracea (Conforto & Contin 2009, Dapont et al 2016 and E. edulis (Nakazono et al 2001, Tsukamoto Filho et al 2001, Ribeiro et al 2011, but little has been found about the behavior of E. precatoria under those conditions. For this reason, more research on adequate cultivation environments is needed, especially in what regards shading levels for the formation of good-quality seedlings.…”
Section: Introductionmentioning
confidence: 99%